Overeducation, performance pay and wages: Evidence from Germany - Mehrzad B. Baktash (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2023)
Overeducated workers are more productive and have higher wages in comparison to their adequately educated coworkers in the same jobs. However, they face a series of challenges in the labor market, including lower wages in comparison to their similarly educated peers who are in correctly matched jobs. Yet, less consensus exists over the adjustment mechanisms to overcome the negative consequences of overeducation. This study examines the hypotheses that overeducated workers sort into performance pay jobs as an adjustment mechanism and that performance pay moderates their wages. Using German Socio-Economic Panel, I show that overeducation associates with a higher likelihood of sorting into performance pay jobs and that performance pay moderates the wages of overeducated workers positively. It also holds in endogenous switching regressions accounting for the potential endogeneity of performance pay. Importantly, the positive role of performance pay is particularly larger for the wages of overeducated women.
Keywords: I21; J24; J31; J33; M52; 330; Performance Pay; Overeducation; Wages; Educational Mismatch; Sorting